The battle of ideas in the Labour Party : from Attlee to Corbyn and Brexit - Batrouni, Dimitri (Bristol University Press, 2020)
Using interviews with key thinkers in the party, this book gives a lively account of the ideological developments and dramas in the Labour party in recent decades. It delves into the totemic battles between hard and soft left, examines key periods of Labour's ideological exhaustion and ideational confusion, and analyses the impacts of Corbynism.